Prophetic imagination, internal armed conflict and utopia in el cerco de lima by Óscar Colchado Lucio - Yamunaqué, Fernando Montalvo (2024)
The purpose of this research is to do an analysis of the elements of the apocalyptic discourse and utopia in El cerco de Lima (2013) by Óscar Colchado Lucio. Building upon the ideas of American theologian Walter Brueggemann, we will demonstrate that the Preacher, a character embodying the traits of a biblical prophet, fulfills the rol of proposing a social utopia within the context of the internal armed conflict in Peru. In that sense, we are interested in highlighting three aspects of this prophetic role: (1) the reworking of biblical symbols with the aim of understanding contemporary social conflicts; (2) the appeal to the language of affliction to expose the crisis denied by the hegemonic order; and (3) the exposition of the fragility of the human condition and the failure of its systems of governance. In that line of thought, the utopia will be shaped as an alternative to the chaos unleashed by political violence.